Can Charter Schools Address Racial Inequities Evidenced in Access to the General Education Classroom? A Longitudinal Study in Chicago Public Schools. (June 2020) - Waitoller, Federico R.; Maggin, Daniel M.
This study presents a longitudinal analysis of racial inequities evidenced in placement patterns in the least restrictive environment (LRE). We compared placement trends in neighborhoods and charter schools for Black and White students receiving special education services (SRSES). Drawing from the concept of institutional isomorphism and using a longitudinal analysis of odds ratio, we examined annual school data from 2008 to 2012 on students' placement in the LRE in Chicago Public Schools (CPS). Our findings indicate that over time charter schools mirror neighborhood schools' (NS) racial inequities evidenced in access to general education classrooms.